Atomic alloys of nickel-platinum on carbon network for methanol oxidation. (May 2022) - Hui, Lan; Xue, Yurui; Xing, Chengyu; Liu, Yuxin; Du, Yuncheng; Fang, Yan; Yu, Huidi; Zhang, Chao; He, Feng; Li, Yuliang
Abstract: We utilize the domain-limiting effect of the porous graphdiyne (GDY) hexagonal ring to control synthesis of single-nickel-atom-alloyed platinum hexagonal nanocrystals (NiPtSAA/GDY) with uniform size approximate to 2.18 nm and atomically lattice distortion. The structure of NiPtSAA/GDY was confirmed by high-angle annular dark-field scanning transmission electron microscopy (HAADF-STEM) and detail characterized and theoretical calculations. The hexagonal nanocrystals showed an excellent mass activity of 4.40 A mg Pt+Ni −1 and specific activity (136.78 mA cm −2 ) and exhibited the greatly enhancement in the durability and activity in MOR. In situ XAFS and XPS measurements indicated that low valence states of Pt in NiPtSAA/GDY were highly resistant to CO poisoning and demonstrated that the valence states were the origin of the activity. Our results provide a solid foundation for the design and synthesis with high dependence on valence and reactivity, while avoiding synergistic CO-poisoning, and also provide a general route for the design of new model catalysts. Graphical Abstract: ga1 Highlights: Single-nickel-atom-alloyed platinum hexagonal nanocrystal shows high activity, selectivity and durability for MOR. The NiPtSAA/GDY shows high mass activity of 4.40 A mgPt+Ni −1 and specific activity of 136.78 mA cm −2 for MOR. We report a general and efficient strategy for fabricated the new model catalysts.